The age of sustainability just transitions in a complex world - Swilling, Mark (Routledge studies in sustainable development, 2020)
With transitions to more sustainable ways of living already underway, this book examines how we understand the underlying dynamics of the transitions that are unfolding. Without this understanding, we enter the future in a state of informed bewilderment. Shedding light on the highly complex challenge of a sustainable and just transition, this book is essential reading for anyone concerned with establishing a more sustainable and equitable world. Ultimately, this is a book about hope, but without easy answers"--